2015
DOI: 10.1152/physiolgenomics.00023.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Gestation under chronic constant light leads to extensive gene expression changes in the fetal rat liver

Abstract: Recent reports account for altered metabolism in adult offspring from pregnancy subjected to abnormal photoperiod, suggesting fetal programming of liver physiology. To generate a pipeline of subsequent mechanistic experiments addressing strong candidate genes, here we investigated the effects of constant gestational light on the fetal liver transcriptome. At 10 days of gestation, dams were randomized in two groups ( n = 7 each): constant light (LL) and normal photoperiod (12 h light/12 h dark; LD). At 18 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…As we reported previously, circadian disruption impacts the fetal transcriptome of heart, liver and adrenal gland in different models of gestational chronodisruption (3032). Our microarray studies in fetal kidney revealed that 1,703 transcripts were differentially expressed, where the most represented Cellular Compartment were “Plasma Membrane” and “Nucleus,” while the main Biological Function targeted was “Regulation of transcription.” Also, we found that the significant enrichment pathways on KEEG were: “Ribosome,” “Viral myocarditis” and “Aldosterone-regulated Na+ reabsorption.” Many of the differentially expressed genes in the CPS kidney have high representation during the embryonic developmental stage; for instance, cellular proliferation, morphogenesis and ECM production, as it has been described in ontogenic kidney array studies (51, 52).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As we reported previously, circadian disruption impacts the fetal transcriptome of heart, liver and adrenal gland in different models of gestational chronodisruption (3032). Our microarray studies in fetal kidney revealed that 1,703 transcripts were differentially expressed, where the most represented Cellular Compartment were “Plasma Membrane” and “Nucleus,” while the main Biological Function targeted was “Regulation of transcription.” Also, we found that the significant enrichment pathways on KEEG were: “Ribosome,” “Viral myocarditis” and “Aldosterone-regulated Na+ reabsorption.” Many of the differentially expressed genes in the CPS kidney have high representation during the embryonic developmental stage; for instance, cellular proliferation, morphogenesis and ECM production, as it has been described in ontogenic kidney array studies (51, 52).…”
Section: Discussionsupporting
confidence: 61%
“…The same RNA was used for validation by RT-qPCR. Ingenuity Pathway Analysis (IPA) and DAVID 6.7 were used for functional genomics analysis of differentially expressed genes as described previously (31, 32). The full data set for global transcription analysis by microarray is available at the following NCBI online repository link (www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE130744).…”
Section: Methodsmentioning
confidence: 99%
“…; Spichiger et al . ). As mentioned, we used the same RNA samples from the microarray analysis to perform the RT‐qPCR validation assays.…”
Section: Methodsmentioning
confidence: 97%
“…Furthermore, because different systems develop at different ontogenetic stages, we hypothesized that the timing of DCCD would differentially impact distinct physiological and behavioral traits. In previous studies, exposing pregnant mice and rats to constant light produced lasting increases in anxiety-like behavior 1315 , with mixed results in learning tasks 1416 and associated hippocampal functions 15, 16 . Likewise, maternal circadian disruption alters offspring metabolic functioning in adulthood 13, 1719 , including the regulation of glucocorticoids 17 and insulin 18 .…”
Section: Introductionmentioning
confidence: 91%